Indian people, caboclos and border guardians: the degradation of the other since the arrival of the European in the Brazilian amazon - Sampaio, Sonia Maria Gomes (2023)
This article aims to analyze, from the idea of inventing the Amazon, the terms used by the Portuguese and Spanish to designate the Other, the native, the caboclo, the indian, during the process of colonization of the Amazon, and how these designations are presented in travel reports and later in the literature of/in the Amazon. To do so, we will use the critical approach of postcolonial studies, mainly the arguments of Henrique Dussel, Neide Gondim, Ana Pizarro, Eduardo Galeano, Hugo Achugar, Albert Memmi, among others, to deal with the colonization of the Amazon, analyzing the terms: indian, caboclo and border guard, employed by colonizers in the Amazon. The results indicate that the use of these terms reveals the perverse strategy of the colonizer in identifying the Other, the different, making him inferior, subjugating him, thus justifying domination, exploitation. These strategies extend to the present day in an even more refined way, therefore, the urgency to reflect and epistemically expose this process, in order to decolonize the look and practices in relation to the natives of/in the Amazon.